ANALISIS PENGARUH PENGATURAN DAYA REAKTIF UNTUK FILTER HARMONIC TERHADAP PERUBAHAN THDi PADA SISTEM TENAGA LISTRIK - I Wayan Rinas; A. A Gede Maharta Pemayun; I Made Suartika (Program Studi Teknik Elektro UNUD, 2020)
Harmonic filters are used to reduce harmonic distortion in electric power systems. Inactive filters, usually the required reactive power (Qc) can be adjusted. In this study, an analysisof the Qc setting on the Active filter was carried out to determine the effectiveness of the filter sothat the THDi (total harmonic distortion) was obtained which was in accordance with the IEEE519-2014 standard (8%). The results of the analysis of the smallest Qc which can still reduceharmonic distortion when meeting the IEEE 519-2014 standard is Qc 55% of the maximumreactive power with THDi for pasa R = 7.38%; S = 7.81%; and T = 5.94%. Control is needed toadjust the Qc on the filter, because the Qc value will continue to change according to theelectric load being operated.